Pola Komunikasi Terapeutik Perawat dan Pasien Hemodialisis - Rini Rinawati (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2008)
This paper is concerned with the dissemination of Healthy Lifestyle information.Healthy Lifestyle which applying food combining approach recently is hailed as a breakthrough in health communication. Meanwhile, the dissemination process consists of message characteristic, communication channel, and range of time period. The innovation on message characteristic involves factors such as relative benefit, compatibility, and complexity. Relative innovation is generated from economy aspect: by applying healthy lifestyle information, it is strongly hoped that human body will become healthy, full of energy, and free from disease. On the other hand, there is difficulty on compatibility factors, due to society’s eating pattern which referred on four-healthy pattern for every meal, not for a whole day. The spread of information need a deep toward lifestyle—add complexity for the matter. The communication channels to widespread this information to the public utilize a combination of interpersonal communication (for consultation), group communication (public speech), and mass communication (print media). Time is also a crucial factor in planning information dissemination.